Akibat Hukum Perkawinan Sirri Ditinjau Dari Hukum Islam Dan Undang-Undang No. 1 Tahun 1974 Tentang Perkawinan - Andri, Muhammad (Fakultas Hukum Universitas Darul Ulum, 2015)
Marriage is a bond between one's inner and outer man with person woman as husband - wife to form a happy home, the eternal popularity of divinity Almighty. The marriage was valid when conducted according to the Law on Religion and belief respectively and in order to have the force of law and apply the power of these marriages must be registered. Reality in all societies there is often a practice of marriage Sirri deemed lawful religion, but does not have the power under the law applicable positive.In this study in trying ffor know how the views of Islamic law and positive law in the implementation of marriage Sirri, the factors that led to marriage Sirri, and how the settlement process of marriage Sirri by positive law.The findings generated in this study are as follows: (1) the basis of marriage Sirri menutut Islamic law is valid, but according to the positive law of marriage does not have the power serve as evidence to ensure legal certainty. (A) major factors that lead to marriage Sirri was done because of lack of knowledge and awareness of the law that marriage is to be registered. (B) completion of the process according to the positive law is the determination of the completion of the ratification of the marriage, as well as with the decision of divorce into one.In order to ensure legal certainty in the face of Sirri marriage problems should be considered carefully whether the marriage is really fixed in accordance with the legislation in force, so that in case of divorce was not until there was a marriage that does not have a marriage certificate. So that people understand the need for a registered marriage tau listed, so do not arise from the law, because marriage Sirri then KUA officials did not hesitate to socialize.